Cheap Does Not Mean Blessing: The Challenges of Modern Agribusiness Economics at Majelis Taklim Al-Usmaniyah, Rawa Gempol, Teluk Naga District, Tangerang Regency - Nandar Gustian; Resi Dazia (International Research and Development for Human Beings (IRDH), 2025)
In the era of globalization and increasingly apparent climate change, challenges to the food system are becoming more complex. Changes in weather patterns, land degradation, and water crises can threaten agricultural productivity, requiring rapid innovation and adaptation so that communities can continue to meet their food needs. The goal of this research and community service is to provide guidance to the students of Pondok Pesantren (Ponpes) Al-Insaniyah, Rawa Gempol, Teluk Naga District, Tangerang Regency, on the importance of meeting economic and food needs through modern agribusiness activities. This research and community service is carried out at Pondok Pesantren (Ponpes) Al-Insaniyah, Rawa Gempol, Teluk Naga District, Tangerang Regency, in August 2025. The method used in this research is direct instruction, through outreach activities between resource persons and participants. The implementation of the activities has been carried out in the form of providing outreach on the importance of economic and food fulfillment through modern agribusiness activities, covering three materials: the importance of affordable and blessed food, economic challenges in realizing modern agribusiness, and ways to start implementing modern agribusiness based on pesantren. A recommendation that can be given is the need for collaboration between higher education institutions and pesantren to realize modern agribusiness based on pesantren, which can strengthen the country's food security.